Question and Answers Forum

All Questions      Topic List

UNKNOWN Questions

Previous in All Question      Next in All Question      

Previous in UNKNOWN      Next in UNKNOWN      

Question Number 33145 by Ahmad Hajjaj last updated on 11/Apr/18

∫_( 0) ^3  (dx/((√(x+1)) + (√(5x+1)))) =

30dxx+1+5x+1=

Commented by prof Abdo imad last updated on 11/Apr/18

I = ∫_0 ^3         (dx/((√(x+1))  +(√(5x+1))))    .ch. (√(x+1)) =t ⇒  I = ∫_1 ^2         ((2tdt)/(t  +(√(5(t^2 −1)+1))))  = ∫_1 ^2        ((2tdt)/(t +(√( 5t^2  −4))))  = ∫_1 ^2       ((2dt)/(1 +(√((5t^2  −4)/t^2 ))))  = ∫_1 ^2         ((2dt)/(1+(√(5 −(4/t^2 )))))  after we use the ch.  (2/t) =(√5) sinx ⇒ (t/2) = (1/((√5) sinx)) ⇒t = (2/((√5) sinx))  dt =−(2/(√5))  ((cosx)/(sin^2 x))  and x =arcsin((2/(t(√5))))  I = ∫_(arcsin((2/(√5)))) ^(arcsin((1/(√5))))          (1/(1+(√5) (√(1−sin^2 x))))  −(2/(√5)) ((cosx)/(sin^2 x))dx  = −(2/(√5))∫_(arcsin((2/(√5)))) ^(arcsin((1/(√5))))        ((cosx)/(sin^2 x(1+(√5) cosx)))dx  ∫_α ^β    −((cosx)/(sin^2 x(1+(√5) cosx))) (by parts)  = [ (1/(sinx))  (1/(1+(√5) cosx))]_α ^β   − ∫_α ^β   (1/(sinx)) (((√5) sinx)/((1+(√5) cosx)^2 ))dx  =(1/(sinβ(1+(√5) cosβ))) − (1/(sinα(1+(√5) cosα)))  −(√5)  ∫_α ^β     (dx/((1+(√5) cosx)^2 ))  and this integral is  calculable by ch. tan((x/2)) =u  ....  α=arcsin((2/(√5))) and β = arcsin((1/(√5))).

I=03dxx+1+5x+1.ch.x+1=tI=122tdtt+5(t21)+1=122tdtt+5t24=122dt1+5t24t2=122dt1+54t2afterweusethech.2t=5sinxt2=15sinxt=25sinxdt=25cosxsin2xandx=arcsin(2t5)I=arcsin(25)arcsin(15)11+51sin2x25cosxsin2xdx=25arcsin(25)arcsin(15)cosxsin2x(1+5cosx)dxαβcosxsin2x(1+5cosx)(byparts)=[1sinx11+5cosx]αβαβ1sinx5sinx(1+5cosx)2dx=1sinβ(1+5cosβ)1sinα(1+5cosα)5αβdx(1+5cosx)2andthisintegraliscalculablebych.tan(x2)=u....α=arcsin(25)andβ=arcsin(15).

Answered by MJS last updated on 11/Apr/18

(1/(a+b))=((a−b)/((a+b)(a−b)))=((a−b)/(a^2 −b^2 ))    (1/((√(x+1))+(√(5x+1))))=(((√(x+1))−(√(5x+1)))/(x+1−5x−1))=  =(((√(5x+1))−(√(x+1)))/(4x))  ∫_0 ^3 (dx/((√(x+1))+(√(5x+1))))=(1/4)[(∫((√(5x+1))/x)dx−∫((√(x+1))/x)dx)]_0 ^3 =              (∫((√(ax+b))/x)dx with b>0)=            =2(√(ax+b))+(√b)×ln∣(((√(ax+b))−(√b))/((√(ax+b))+(√b)))∣    =(1/4)[((2(√(5x+1))+ln∣(((√(5x+1))−1)/((√(5x+1))+1))∣)−(2(√(x+1))+ln∣(((√(x+1))−1)/((√(x+1))+1))∣))]_0 ^3 =  =(1/4)[2((√(5x+1))−(√(x+1)))+ln((√(5x+1))−1)−ln((√(5x+1))+1)−ln((√(x+1))−1)+ln((√(x+1))+1)]_0 ^3 =  =(1/4)[2((√(5x+1))−(√(x+1)))+ln(((√(x+1))+1)/((√(5x+1))+1))+ln(((√(5x+1))−1)/((√(x+1))−1))]_0 ^3 =            lim_(x→0) (((√(5x+1))−1)/((√(x+1))−1))=5  =1+(1/2)ln (3/5)

1a+b=ab(a+b)(ab)=aba2b21x+1+5x+1=x+15x+1x+15x1==5x+1x+14x30dxx+1+5x+1=14[(5x+1xdxx+1xdx)]03=(ax+bxdxwithb>0)==2ax+b+b×lnax+bbax+b+b=14[((25x+1+ln5x+115x+1+1)(2x+1+lnx+11x+1+1))]03==14[2(5x+1x+1)+ln(5x+11)ln(5x+1+1)ln(x+11)+ln(x+1+1)]03==14[2(5x+1x+1)+lnx+1+15x+1+1+ln5x+11x+11]03=limx05x+11x+11=5=1+12ln35

Terms of Service

Privacy Policy

Contact: info@tinkutara.com